HYPERNUCLEAR MATTER IN COMPACT STARS - Sedrakian, A.D. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We discuss the recently developed energy density functional for hypernuclear matter, which is based on simultaneous calculation of heavy single-Λ hypernuclei and compact stars containing hypernuclear core. The nucleonic matter is described in terms of a density-dependent parametrization of nucleon-meson couplings, whereas the hyperonmeson couplings are deduced from the octet model. We identify the parameter space of hyperon-meson couplings for which massive stellar configurations with M ≤ 2.1 M_ exist and at the same time the laboratory Λ-hypernuclear data can be described.